Failure to Reach a Consensus in Polypharmacy Definition: An Obstacle to Measuring Risks and Impacts—Results of a Literature Review - Taghy N; Cambon L; Cohen JM; Dussart C (Dove Medical Press, 2020)
Najwa Taghy, 1 Linda Cambon, 2 Jean-Marie Cohen, 3 Claude Dussart 4 1Laboratory P2S (Health Systemic Process), University of Lyon, University Claude Bernard of Lyon 1, Lyon, EA4129, France; 2Research Chair in Prevention, University of Bordeaux, ISPED, Inserm, Bordeaux Population Health Research Center, Team Methods for Population Health Intervention Research, Bordeaux, France; 3Open Rome, Paris, France, Laboratory P2S (Health Systemic Process), University of Lyon, University Claude Bernard Lyon 1, EA4129, France; 4Lyon Public Hospices, Central Pharmacy, Laboratory P2S (Health Systemic Process), University of Lyon, University Claude Bernard Lyon 1, EA4129, FranceCorrespondence: Najwa TaghyUniversity of Lyon, University Claude Bernard Lyon 1, Laboratory P2S (Health Systemic Process), Lyon EA4129, FranceTel +33 633740378Email najwa.taghy@gmail.comIntroduction: The risk of polypharmacy is on the rise in most industrialized countries, threatening to burden their health systems. Although many definitions exist and numerous concepts are found in literature as synonyms, the phenomenon of polypharmacy remains poorly defined. The aim of this literature review is to provide an overview of available definitions of polypharmacy, to analyse their convergences and divergences and to discuss the consequences on the assessment of the problem.Methods: A literature review was conducted to identify all published systematic reviews on definitions of polypharmacy available via Scopus and Pubmed databases. The Assessment of Multiple Systematic Reviews (AMSTAR) tool was used to appraise the methodological quality of the selected reviews. Available definitions and other characteristics were extracted; summarised in a table and analysed.Results: Six systematic reviews were identified. They were published between 2000 and 2018. Three focussed on definitions of polypharmacy in the elderly; two in the general population and one in children. The strategy adopted in reviews is more rigorous in the most recent ones. However, they remain, at best, partially exhaustive. The definitions found in the literature used two main approaches, either (i) quantitative, applying varying thresholds and types of polypharmacy based on the number of medications being taken by the patient (ii) qualitative, based on the clinical indications and effects of a given drug regimen, with a growing number of characteristics to describe polypharmacy. The term “inappropriate” is increasingly associated with polypharmacy especially in studies that aimed to use this definition to identify possible solutions for healthcare providers in the field related to aging.Conclusion: This review confirms a high variability and an evolution in the approaches defining “polypharmacy” in the absence of a consensus following standardized criteria. That makes it very difficult to estimate and measure the outcomes associated with this phenomenon.Keywords: polypharmacy, definition, literature review